MULTIDIMENSIONAL FAMILY THERAPY FOR YOUNG ADOLESCENT SUBSTANCE ABUSE IN INDONESIAN PRISONERS - Amar Akbar; Deni Wahyuningsih (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Research has established the dangers of early onset substance use for young adolescents and its links to a host of developmental problems. Because critical developmental detours can begin or be exacerbated during early adolescence, specialized interventions that target known risk and protective factors in this period are needed. This controlled trial (n=50) provided an experimental test comparing multidimensional family therapy (MDFT) and a peer group intervention with young teens. Participants were clinically referred, were of low income, and were mostly ethnic minority adolescents (average age 13.73 years). Treatments were manual guided, lasted 4 months, and were delivered by community agency therapists in clinical prisioners. Adolescents and parents were assessed at intake, at 6-weeks post-intake, at discharge, and at 3 and 6 months following treatment intake. Latent growth curve modeling analyses demonstrated the superior effectiveness of MDFT over the 6-month follow-up in reducing substance use (effect size: substance use frequency, d= 0.77; substance use problems, d =0.74), delinquency (d = 0.31), and internalized distress (d = 0.54), and in reducing risk in family, peer, and school domains (d = 0.27, 0.67, and 0.35, respectively) among young adolescents.